Possible role for green tea in ovarian cancer prevention - Lee, Andy; Fraser, Michelle; Binns, Colin (Future Medicine, 2005)
Ovarian cancer is the leading cause of death from gynecologic cancer. Tea, especially green tea, has shown promise in the prevention of several cancers. Green tea contains a number of compounds, including polyphenols, that have chemopreventive properties. There is much evidence from in vitro and animal studies suggesting that components of tea are associated with decreased risk or progression of ovarian cancer. However, epidemiologic studies have generated inconsistent results. Recent research conducted in China reported reduced risk of ovarian cancer and increased survival post diagnosis with green tea consumption. This review presents emerging evidence and the authors' perspectives on the role of green tea in ovarian cancer prevention.